Inovasi Anak Lantip Penguatakuntabilitas Pelayanan Kependudukan di Kabupaten Wonogiri - Ilham Maulana Eka; Tri Yuniningsih; Dyah Lituhayu; Teuku Afrizal (Universitas Medan Area, 2023)
This article aims to show the results of innovation program Anak Lahir Administrasi Kependudukan Tertib (ANAK LANTIP) which has implemented Tanda Tangan Elektronik (TTE) on Birth Certificates and Family Cards. The problem is devoted to the usefulness of the ANAK LANTIP program because in this program it will increase the accountability of implementing agents as an obligation to manage resources, report and publish all activities and activities related to the use of public resources. To approach this problem, the theory of reference from Edy Sutrisno (2007) is used, namely the theory of program effectiveness. This theory contains understanding of the program, right on target, on time, achieving goals, and real change. The data were collected through questionnaires, observation, interviews, and document review and were analyzed qualitatively through interactive analysis, critical analysis, and comparative analysis. This study concludes that the effevtiveness of Program Inovasi Anak Lahir Administrasi Kependudukan Tertib (ANAK LANTIP) in Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil), Wonogiri Regency has not been achieved. The implication of this research is that the community must be proven by indicators of socialization that have not been achieved, in implementing Program Inovasi Anak Lahir Administrasi Kependudukan Tertib (ANAK LANTIP) carried out by Disdukcapil still using manual methods, and not yey utilizing technological sophistication and social media so that innovation in this service have not been able to convey to the whole community.